Urgency and Mechanism of Structuring Regional Regulations with the Omnibus Law Method - Rijadi, Prasetijo; Indey, Marthen; Sujono, Imam (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
Structuring regional regulations become necessary as more and more the disclosure of various regulatory problems in the region, both regarding with the amount and material of the load. In an effort to encourage structuring regulations in the regions, this article proposes the use of the omnibus method law in the formation of regional regulations through discussion of urgency and mechanisms the use of omnibus law in the formation of regional regulations. The omnibus law itself is a method or technique in the formation of legislation by establishing a rule to change, revoke, or pass several regulations at once. Method This is worthy of consideration for use in structuring local use regulations overcoming the large number of regional regulations and some of them are problematic in substance. At the local regulatory level, this method is also urgent in order to respond to the Employment Creation Act, which was previously established using the omnibus law method, considering this Law and its implementing regulations require improvements to the regional regulations so that synchronous and harmonious. The mechanism that can be taken is an inventory and analysis of several regional regulations with similar or cognate content to be later formed and compiled into one regional regulation. Various regional regulations whose cargo materials have been combined must be declared revoked and not applies again, in order to make it easier to use compared to just make changes or revoke some articles and insert several new articles as carried out in the Job Creation Law.